2001
DOI: 10.3366/saj.2001.23.2.91
|View full text |Cite
|
Sign up to set email alerts
|

A Prehistoric Ford near Rough Castle, Falkirk

Abstract: This report presents the results of the excavation of a stone ford laid across the base of a small stream valley near Rough Castle, Falkirk. It was discovered during an opencast coal mining project. Radiocarbon dates and pollen analysis of deposits overlying the ford combine to indicate a date for its construction no later than the early first millennium cal BC. Interpreting this evidence was not straightforward and the report raises significant issues about site formation processes and the interpretation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Unusually for regions of the British Isles heavily settled by Roman times, central Scottish rivers seem not to have been highly active in the Roman Iron Age, and their catchments seemingly not actively eroding. This interpretation is supported within a small anonymous stream valley descending to the River Carron east of Rough Castle (illus 2; Hamilton et al 2002), which showed peat with very little eroded mineral matter to have accumulated above a stone-lined ford after c 600 cal bc, probably through the Roman Iron Age. Lake basins provide other data sources on the intensity of soil erosion (Edwards & Whittington 2001).…”
Section: River Valleys and Geomorphic Activitymentioning
confidence: 85%
“…Unusually for regions of the British Isles heavily settled by Roman times, central Scottish rivers seem not to have been highly active in the Roman Iron Age, and their catchments seemingly not actively eroding. This interpretation is supported within a small anonymous stream valley descending to the River Carron east of Rough Castle (illus 2; Hamilton et al 2002), which showed peat with very little eroded mineral matter to have accumulated above a stone-lined ford after c 600 cal bc, probably through the Roman Iron Age. Lake basins provide other data sources on the intensity of soil erosion (Edwards & Whittington 2001).…”
Section: River Valleys and Geomorphic Activitymentioning
confidence: 85%
“…Other aspects of Bronze Age life have been revealed by developer-funded fieldwork. At Rough Castle, Falkirk, a cobble layer discovered beneath peat has been interpreted as a ford across a filled-in water channel (Hamilton et al 2001). This was dated to the early first millennium bc.…”
Section: A Summary Of the Bronze Age Evidencementioning
confidence: 99%